A novel mutation (c.1010G>T; p.R337L) in TP63 as a cause of split‐hand/foot malformation with hypodontia. (30th August 2019) - Jin, Jie‐Yuan; Zeng, Lei; Li, Ke; He, Ji‐Qiang; Pang, Xiaoyang; Huang, Hao; Xiang, Rong; Tang, Ju‐Yu
Abstract: Background: Tumor protein p63 (TP63)‐related disorders can be divided into at least six categories, including ectrodactyly‐ectodermal dysplasia‐cleft lip/palate syndrome 3 (EEC syndrome 3), ankyloblepharon‐ectodermal defects‐cleft lip/palate syndrome (AEC syndrome), acro‐dermo‐ungual‐lacrimal‐tooth syndrome (ADULT syndrome), limb‐mammary syndrome (LMS), Rapp–Hodgkin syndrome (RHS) and split‐hand/foot malformation 4 (SHFM4), and are all a result of heterozygous mutations of TP63 . The phenotypes of TP63‐related disorders broadly involve ectodermal dysplasias, acromelic malformation and orofacial cleft. SHFM and hypodontia are prominent clinical manifestations of TP63‐related disorders. Methods: The present study investigated a family with SHFM and hypodontia; determined the sequences of DLX5, WNT8B, WNT10B, BHLHA9, CDH3, DYNC1I1 and FGFR1 ; and performed single nucleotide polymorphism‐array analysis. We detected the mutation by multiple sequence alignments and a bioinformatic prediction. Results: We identified a novel missense mutation of TP63 (c.1010G>T; R337L) in the family without mutations of DLX5, WNT8B, WNT10B, BHLHA9, CDH3, DYNC1I1, FGFR1 and copy number variants causing SHFM. Conclusions: A mutation of TP63 (c.1010G>T; R337L) leads to SHFM with hypodontia. The identification of this mutation expands the spectrum of known TP63 mutations and also may contribute to novel approaches for the genetic diagnosis and counseling of families with TP63‐related disorders.